Sistem Informasi Pengaduan Masyarakat Program Keluarga Harapan Kota Pekanbaru (Studi Kasus: Dinas Sosial dan Pemakaman Kota Pekanbaru) - Noorvina Rosa; Anofrizen Anofrizen (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2016)
Department of Social and Funeral Pekanbaru is the government agency in ministry of general public. Dinsoskam has a grant program to boost household spending very poor namely Family Expectation Program (PKH) .In the complaints process implementation of PKH is done manually and there are some constraints, as the difficulty of doing recapitulation data in hardcopy form, the complaint was not recorded perfectly, it is difficult to find data, frequent double counting and incompatibility of the reporting of data, and data loss. The purpose of this study to design a Public Complaint Information System Family Hope Program which uses the database as a data storage  that can facilitate the search data, the production and storage, and replaces the use of the complaints system manual. The system development methods used are Agile and tools to design in this study using UML, interface design to coding using PHP, to arrive at the functional testing phase system using blackbox testing. Based on the test results blackbox this system can be used properly. This system can be run as expected as advice for Department of Social and Funeral Pekanbaru in managing complaint PKH is web-based.                                                                                           Keywords: Agile, blackbox, information system for public complaints , PHP, UML